Environmental pollution, economic growth and institutional quality: Exploring the nexus in Nigeria - Samuel Egbetokun; Evans Osabuohien; Temidayo Oladiran Akinbobola; Olaronke Toyin Onanuga; Obindah Gershon; Victoria Okafor (African Governance and Development Institute (AGDI), 2019)
The interaction between environmental pollution and economic growth determines the achievement of the green growth objective of developing economies. An economy turns around the inverted U-shaped Environmental Kuznets Curve (EKC) when pollution is effectively dampened by social, political and economic factors as such economy grows. Thus, this study examines the EKC considering the impact of institutional quality on six variables of environmental pollution [carbon dioxide (CO2), Nitrous Oxide (N2O), Suspended Particulate Maters (SPM), Rainfall, Temperature and Total Green House Emission (TGH)] using the case of Nigeria. The EKC model includes population density, education expenditure, foreign direct investment, and gross domestic investment as control variables, and it was analysed using the Auto Regressive Distribution Lag (ARDL) econometric technique, which has not been applied in the literature on Nigeria. The results, inter alia, indicate that there is EKC for CO2 and SPM. This implies that the green growth objective can be pursued in Nigeria with concerted efforts. Other environmental pollution indicators did not exert significant influence on economic growth. Therefore, it is recommended that Nigeria's institutional quality be strengthened to limit environmental pollution in light of economic growth.
Keywords: C52; O38; O40; O55; P37; 330; EKC; Economic Growth; Environmental Pollution; Institutional Quality